Captain America : 3-movie collection [videorecording (Blu-Ray)] - Evans, Chris, 1981-; Downey, Robert, Jr., 1965-; Johansson, Scarlett, 1984-; Jones, Tommy Lee, 1946-; Weaving, Hugo, 1960-; Atwell, Hayley, 1982-; Jackson, Samuel L; Redford, Robert; Mackie, Anthony, 1978- (Buena Vista Home Entertainment, 2021)
Captain America, The First avenger: Captain America leads the fight for freedom in the action-packed blockbuster starring Chris Evans as the ultimate weapon against evil! When a terrifying force threatens everyone across the globe, the world's greatest soldier wages war on the evil Hydra organisation, led by the willainous Red Skull.